Mirror-Mirror on the Wall, What Job Mismatch Measurements of All? - Borhan Sareya, Abdullah; Mohd Sabrun, Ibrahim (2022)
In today’s labour market, job mismatch is not a new issue. It has been addressed thoroughly. The frequency and consequences of job mismatch are investigated in a small but growing body of literature. Most job mismatch research has been motivated by concerns that the rise in labour-force educational attainment may have outpaced the rise in jobs for more educated people. Job mismatch is frequently cited as a significant source of labour market inefficiency. However, job mismatch is difficult to measure, define, and comprehend. Therefore, this paper conducts bibliometric analysis, content analysis, and thematic analysis using a systematic literature review to identify trends and outcomes of studies on job mismatch. The PRISMAguided literature review search examines 161 Scopus-indexed articles. As a result, this paper identifies the most influential authors and articles, leading journals and countries, and research cluster networks. This review also discusses job mismatch measurement and the future direction of job mismatch studies. Furthermore, this review paper provides critical and beneficial insights for policymakers and researchers.